Palliative care needs in patients hospitalized with heart failure (PCHF) study: rationale and design. (19th March 2015) - Campbell, Ross T.; Jackson, Colette E.; Wright, Ann; Gardner, Roy S.; Ford, Ian; Davidson, Patricia M.; Denvir, Martin A.; Hogg, Karen J.; Johnson, Miriam J.; Petrie, Mark C.; McMurray, John J.V.
Abstract Aims The primary aim of this study is to provide data to inform the design of a randomized controlled clinical trial (RCT) of a palliative care (PC) intervention in heart failure (HF). We will identify an appropriate study population with a high prevalence of PC needs defined using quantifiable measures. We will also identify which components a specific and targeted PC intervention in HF should include and attempt to define the most relevant trial outcomes. Methods An unselected, prospective, near‐consecutive, cohort of patients admitted to hospital with acute decompensated HF will be enrolled over a 2‐year period. All potential participants will be screened using B‐type natriuretic peptide and echocardiography, and all those enrolled will be extensively characterized in terms of their HF status, comorbidity, and PC needs. Quantitative assessment of PC needs will include evaluation of general and disease‐specific quality of life, mood, symptom burden, caregiver burden, and end of life care. Inpatient assessments will be performed and after discharge outpatient assessments will be carried out every 4 months for up to 2.5 years. Participants will be followed up for a minimum of 1 year for hospital admissions, and place and cause of death. Methods for identifying patients with HF with PC needs will be evaluated, and estimates of healthcare utilisation performed. Conclusion By assessing the prevalence of these needs, describing how these needs change over time, and evaluating how best PC needs can be identified, we will provide the foundation for designing an RCT of a PC intervention in HF.